Integrating Resource-Based View Theory with Islamic Enterpreunership Ethics: A Sharia Perspective on MSME Resilience - Muhammad Imtiaz Humed; Ahmad Djalaluddin (STAI Al-Mas'udiyah, 2026)
In order to increase the resilience of Micro, Small, and Medium-Sized Enterprises (MSMEs) in Indonesia, this study intends to investigate the integration of Islamic entrepreneurial principles with Resource-Based View (RBV) theory. MSMEs are crucial to the economy, but they face obstacles such a lack of funding, poor managerial skills, and reliance on outside influences. RBV highlights the value of intangible resources including reputation, managerial skills, and customer connections, whereas prior research emphasizes the significance of internal resource management in sustaining corporate sustainability. However, the Islamic-based ethical component which might promote corporate sustainability is frequently disregarded. The Sharia-Based Business Resilience approach, which combines RBV with Islamic business virtues including integrity, reliability, justice, and social responsibility, is a novel approach that this study suggests. These moral principles complement the RBV's VRIN (Valuable, Rare, Inimitable, Non-Substitutable) standards, offering MSMEs strategic benefits that bolster their resilience, particularly in times of economic turmoil. This study provides a more thorough method to comprehending and enhancing the sustainability and adaptability of MSMEs by merging these two frameworks. It also gives theoretical insights and useful recommendations for business actors and policymakers in creating long-term business success.